2012
DOI: 10.1186/1475-9276-11-77
|View full text |Cite
|
Sign up to set email alerts
|

Social inequalities in health: measuring the contribution of housing deprivation and social interactions for Spain

Abstract: IntroductionSocial factors have been proved to be main determinants of individuals’ health. Recent studies have also analyzed the contribution of some of those factors, such as education and job status, to socioeconomic inequalities in health. The aim of this paper is to provide new evidence about the factors driving socioeconomic inequalities in health for the Spanish population by including housing deprivation and social interactions as health determinants.MethodsCross-sectional study based on the Spanish sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Socioeconomic disparities have been shown to be associated with a greater level of all-cause mortality [3], and although treating current disease is an urgent priority, we should not disregard taking action on the underlying social determinants of health [4]. The literature has evidenced the importance of socioeconomic conditions on health and has demonstrated that socioeconomic adversity is a modifiable risk factor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Socioeconomic disparities have been shown to be associated with a greater level of all-cause mortality [3], and although treating current disease is an urgent priority, we should not disregard taking action on the underlying social determinants of health [4]. The literature has evidenced the importance of socioeconomic conditions on health and has demonstrated that socioeconomic adversity is a modifiable risk factor [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…This study provided evidence that health is positively associated with variables related to social support. Prior research in Spain has shown that the higher the frequency of contacts with family members or friends, the lower the probability of having health problems [ 35 ]. This may be related to attitudes of family or friends in the Spanish society.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to geographic inequalities, health inequalities associated with socioeconomic factors such as education, income, and work status have persisted over time 40 . For example, evidence has shown an association between social class and chronic diseases, more prevalent in persons with less schooling, as well as inequalities associated with risk factors like smoking and alcohol consumption 41 .…”
Section: Spainmentioning
confidence: 99%